Income, income inequality and mortality in metropolitan regions of Brazil: an exploratory approach - CAVALCANTE-FRANÇA, Mardone; ANTUNES-PAES, Neir (Papeles de Población, 2007)
The goal of this study is to perform an empirical verification of the hypotheses of absolute income and income inequality for 16 metropolitan regions of Brazil (MRB), based on data from the Demographic Census of 2000 and vital statistics from 1999-2001 (deaths by age, sex and causes of death). To test the hypotheses, multiple regression models were adjusted for each independent variable and the statistical significance of regression coefficients corresponding to each hypothesis was verified. The results suggest that mean income is the determinant health factor for the population residing in MRB and not income inequality.